Hemodialysis Duration with Levels of Hemoglobin, Hematocrit, Serum Iron and Total Iron Binding Capacity on Chronic Kidney Disease - Supriati Wila Djami; Marni Tangkelangi (JURNAL INFO KESEHATAN, 2021)
The correlation of the length of time undergoing hemodialysis with the levels of hemoglobin, hematocrit, serum iron and total iron binding capacity in patients with chronic kidney disease at RSUD Prof. Dr. W. Z. Johannes Kupang. People with chronic kidney disease who are performing Hemodialysis suffer from anemia. Blood loss during the hemodialysis process is affected by frequent blood sampling for laboratory tests. To diagnose the occurrence of iron deficiency, anemia laboratory tests such as complete blood, serum iron (SI), TIBC, transferrin saturation, and serum ferritin can be conducted. The objective of this study is to determine the correlation between the length of undergoing Hemodialysis with the levels of Hemoglobin, Hematocrit, Serum Iron, and Total Iron Binding Capacity (TIBC) in patients with chronic kidney disease in RSUD Prof. Dr.W. Z Johannes Kupang. This study employed an anon-reactive research design or unobtrusive research based on secondary data derived from medical record records at RSUD Prof. Dr.W. Johannes in August - September 2019 on 92 hemodialysis patients who met the inclusion criteria. The collected data were calculated with the SPSS application, while the correlation analysis between variables was performed by administering a linear regression analysis test. Ninety-two (92) respondents were obtained by employing the purposive sampling technique. The majority of patients with chronic kidney disease undergoing Hemodialysis were men (57.6%) with ages 39 - 59 years (63.0%), and the majority of patients undergoing Hemodialysis in patients with chronic kidney failure (CKD) were <12 months (41.3%). It was discovered that there was no relationship between the length of Hemodialysis with hemoglobin, hematocrit, serum iron, and total iron-binding capacity levels in patients with chronic kidney disease (CKD).